Students' Mathematical Understanding of Online Learning: Evaluation of Triangular and Rectangular Materials - Santosa, Farah Heniati; Samsuriadi, Samsuriadi; Hadi, Salman; Jinan, Riadil; Astutiyani, Lia Maria (Universitas Muhammadiyah Mataram, 2022)
The purpose of this research is to find out a comprehensive picture of students' mathematical understanding in the online learning process, especially in the triangle and quadrilateral material. The study was conducted on 20 students in MTs. Nurul Islah Gegelang. The qualitative research method was chosen. Interactive analysis is applied to obtain in-depth information related to interpreting research findings. Data collection is done by using zoom meeting. The research data are in the form of test scores for mathematical understanding abilities, observation sheets related to the online learning process carried out and in-depth interviews to determine students' mathematical understanding abilities. The results of the study showed that, out of 20 students, only 8 students scored 30 and 12 were below. The ability of students' mathematical understanding in the online learning process was still very poor, especially in the concept of triangles and quadrilaterals. Students' understanding is still limited to memorizing properties without understanding in detail the characteristics of each flat shape. Students still have difficulty in applying formulas to triangles and quadrilaterals in solving problems.